2020
DOI: 10.2196/20709
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-Based Programs for Patients With Cancer via eHealth and Mobile Health: Systematic Review and Synthesis of Quantitative Research

Abstract: Background eHealth mindfulness-based programs (eMBPs) are on the rise in complex oncology and palliative care. However, we are still at the beginning of answering the questions of how effective eMBPs are and for whom, and what kinds of delivery modes are the most efficient. Objective This systematic review aims to examine the feasibility and efficacy of eMBPs in improving the mental health and well-being of patients with cancer, to describe intervention… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 123 publications
1
47
0
1
Order By: Relevance
“…The results of this study suggest that the See Me Serene app is feasible to deliver and test. Our results appear to be similar to other studies that have found mHealth apps feasible to deliver and easy to disseminate [52][53][54][55]. We met or surpassed all of our feasibility benchmarks, including the recruitment and retention of participants and the collection of both self-report data and biochemical samples.…”
Section: Feasibilitysupporting
confidence: 86%
See 2 more Smart Citations
“…The results of this study suggest that the See Me Serene app is feasible to deliver and test. Our results appear to be similar to other studies that have found mHealth apps feasible to deliver and easy to disseminate [52][53][54][55]. We met or surpassed all of our feasibility benchmarks, including the recruitment and retention of participants and the collection of both self-report data and biochemical samples.…”
Section: Feasibilitysupporting
confidence: 86%
“…Although this study was not designed to test efficacy, we found significant reductions in all outcome variables with small to medium effect sizes. The evidence regarding effectiveness of mHealth apps is limited and mixed [53,54,[56][57][58][59][60][61][62][63][64]. While several randomized controlled trials have shown these apps to be effective at reducing stress, anxiety, depression, or PTSD symptoms [53,54,57,59], some have not reported positive results [60,61,64].…”
Section: Potential Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…As one of internet-delivered Mindfulness-Based Interventions (iMBIs), internet-based MBSR (iMBSR) has also shown to be efficacious in treating psychological distress among cancer patients ( 25 ). Therefore, in the current study, iMBSR was conducted among survivors of BC during the 2 months from February to March, 2021, during which the COVID-19 outbreak was announced and followed by nation-wide lockdown in February, 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding psychological interventions based on mindfulness, only 1 RCT study compared MBCT and eMBCT with usual care and found that MBCT and eMBCT were equally efficacious compared with treatment as usual in reducing FCR [27,76,77]. In general, face-to-face and web-based interventions reduced FCR at posttreatment [28][29][30][31][32][33]53].…”
Section: Principal Findingsmentioning
confidence: 99%